2015
DOI: 10.1021/acs.jced.5b00064
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibria for Binary Systems of Diethyl Carbonate + Propylene Carbonate, Diethyl Carbonate + Propylene Glycol, and Ethanol + Propylene Carbonate at 101.3 kPa

Abstract: Isobaric vapor–liquid equilibrium (VLE) data at 101.3 kPa were measured using a dynamic recirculating still for the binary systems of diethyl carbonate + propylene carbonate, diethyl carbonate + propylene glycol, and ethanol + propylene carbonate. The thermodynamic consistency of the VLE data has been checked with the Herington integral and point-to-point test methods. All of the equilibrium data were correlated with the nonrandom two liquid and the universal quasichemical models. Good agreement between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 42 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Carbonate esters have a wide range of applications as solvents in various chemical and pharmaceutical industries, such as diethyl carbonate (DEC), which is typically used as a gasoline additive or a co-additive with primary alcohols. Meanwhile, engine performance studies using esters as gasoline additives reported better performance and reduced smoke.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate esters have a wide range of applications as solvents in various chemical and pharmaceutical industries, such as diethyl carbonate (DEC), which is typically used as a gasoline additive or a co-additive with primary alcohols. Meanwhile, engine performance studies using esters as gasoline additives reported better performance and reduced smoke.…”
Section: Introductionmentioning
confidence: 99%